Immunotherapy-related adverse events in real-world patients with advanced non-small cell lung cancer on chemoimmunotherapy: a Spinnaker study sub-analysis - Anpalakhan, Shobana; Huddar, Prerana; Behrouzi, Roya; Signori, Alessio; Cave, Judith; Comins, Charles; Cortellini, Alessio; Addeo, Alfredo; Escriu, Carles; McKenzie, Hayley; Barone, Gloria; Murray, Lisa; et al. (Frontiers in Oncology, 2023)
Background: The Spinnaker study evaluated survival outcomes and prognostic factors in patients with advanced non-small cell lung cancer receiving first-line chemoimmunotherapy in the real world. This sub-analysis assessed the immunotherapy-related adverse effects (irAEs) seen in this cohort, their impact on overall survival (OS) and progression-free survival (PFS) and related clinical factors. Methods: The Spinnaker study was a retrospective multicentre observational cohort study of patients treated with first-line pembrolizumab plus platinum-based chemotherapy in six United Kingdom and one Swiss oncology centres. Data was collected on patient characteristics, survival outcomes, frequency and severity of irAEs and peripheral immune-inflammatory blood markers, including the neutrophil-to-lymphocyte ratio (NLR) and systemic immune-inflammation index (SII). Results: 308 patients were included; 132 (43%) experienced any grade irAE, 100 (32%) Grade 1-2 and 49 (16%) Grade 3-4 irAEs. The median OS in patients with any grade irAES was significantly longer (17.5 months [95% CI: 13.4-21.6 months]) than those without (10.1 months [95% CI 8.3-12.0 months]) (p<0.001), either if Grade 1-2 (p=0.003) or Grade 3-4 irAEs (p=0.042). The median PFS in patients with any Grade irAEs was significantly longer (10.1 months [95% CI: 9.0-11.2 months]) than those without (6.1 months [95% CI 5.2-7.1 months]) (p<0.001), either if Grade 1-2 (p=0.011) or Grade 3-4 irAEs (p=0.036). A higher rate of irAEs of any grade and specifically Grade 1-2 irAEs correlated with NLR <4 (p=0.013 and p=0.018), SII <1440 (p=0.029 ad p=0.039), response to treatment (p=0.001 and p=0.034), a higher rate of treatment discontinuation (p<0.00001 and p=0.041) and the NHS-Lung prognostic classes (p=0.002 and p=0.008). Conclusions: These results confirm survival outcome benefits in patients with irAEs and suggest a higher likelihood of Grade 1-2 irAEs in patients with lower NLR or SII values or according to the NHS-Lung score.